A Triadic Neurocognitive Approach to Addiction for Clinical Interventions - Noel, Xavier; Brevers, Damien; Bechara, Antoine (Frontiers in Psychiatry, 2013)
According to the triadic neurocognitive model of addiction to drugs (e.g., cocaine) and non-drugs (e.g., gambling), weakened “willpower” associated with these behaviours is the product of an abnormal functioning in one or more of three key neural and cognitive systems: (1) an amygdala-striatum dependent system mediating automatic, habitual, and salient behaviours; (2) a prefrontal cortex dependent system important for self-regulation and forecasting the future consequences of a behaviour and (3) an insula dependent system for the reception of interoceptive signals and their translation into feeling states (such as urge and craving), which in turn plays a strong influential role in decision-making and impulse control processes related to uncertainty, risk, and reward. The described three-systems account for poor decision-making (i.e., prioritizing short-term consequences of a decisional option) and stimulus-driven actions, thus leading to a more elevated risk for relapse. Finally, this article elaborates on the need for “personalized” clinical model-based interventions targeting interactions between implicit processes, interoceptive signalling, and supervisory function aimed at helping individuals become less governed by immediate situations and automatic prepotent responses, and more influenced by systems involved in the pursuit of future valued goals.